2008
DOI: 10.1016/j.cell.2008.01.018
|View full text |Cite
|
Sign up to set email alerts
|

FoxA1 Translates Epigenetic Signatures into Enhancer-Driven Lineage-Specific Transcription

Abstract: Complex organisms require tissue-specific transcriptional programs, yet little is known about how these are established. The transcription factor FoxA1 is thought to contribute to gene regulation through its ability to act as a pioneer factor binding to nucleosomal DNA. Through genome-wide positional analyses, we demonstrate that FoxA1 cell type-specific functions rely primarily on differential recruitment to chromatin predominantly at distant enhancers rather than proximal promoters. This differential recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

72
976
7
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 897 publications
(1,066 citation statements)
references
References 53 publications
72
976
7
5
Order By: Relevance
“…However, another study showed that reduction of H3K4me1 and H3K4me2 impaired FoxA binding in the breast cancer cell line MCF7 (Lupien et al 2008). Altogether, it appears that active histone modifications may enhance pioneer factor binding to chromatin but are not necessarily required for the factor's initial engagement.…”
Section: Positive Chromatin Features For Pioneer Factor Bindingmentioning
confidence: 99%
“…However, another study showed that reduction of H3K4me1 and H3K4me2 impaired FoxA binding in the breast cancer cell line MCF7 (Lupien et al 2008). Altogether, it appears that active histone modifications may enhance pioneer factor binding to chromatin but are not necessarily required for the factor's initial engagement.…”
Section: Positive Chromatin Features For Pioneer Factor Bindingmentioning
confidence: 99%
“…FOX family transcription factors influence ERα-regulated transcription by interaction with the ERα protein, as exemplified by FOXA1 [3]. Recent genome-wide studies aimed at identifying ERα and androgen receptor (AR) binding sites have shown that FOXA1 plays a role in regulating both of these nuclear receptor networks [4,5]. FOXA1 is recognized as a pioneer transcription factor because chromatin binding by this protein can enable subsequent binding by the estrogen and androgen receptors [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent genome-wide studies aimed at identifying ERα and androgen receptor (AR) binding sites have shown that FOXA1 plays a role in regulating both of these nuclear receptor networks [4,5]. FOXA1 is recognized as a pioneer transcription factor because chromatin binding by this protein can enable subsequent binding by the estrogen and androgen receptors [5,6]. Of other FOX family members, FKHR (also known as FOXO1A) also binds directly to ERα and increases its transactivation through an estrogen response element [7].…”
Section: Introductionmentioning
confidence: 99%
“…Ces changements épigénomiques résument donc la perte de différenciation observée dans les cellules cancéreuses. Les enhancers dirigent, via la modulation de l'expression des gènes, le phéno-type cellulaire [6][7][8]. Ainsi, l'acquisition ou la perte de ces éléments devrait se traduire par l'altération du programme transcriptionnel normal.…”
Section: Resultsunclassified
“…De plus, l'acétylation de la lysine 27 de l'histone H3 (H3K27ac) est associée à l'activité de ces éléments régulateurs [6,7]. La comparaison de la localisation de cette signature chromatinienne dans différents types cellulaires a permis de confirmer la nature spécifique des enhancers pour une cellule donnée [6][7][8]. Ceux-ci sont donc le déterminant majeur de l'expression du programme transcriptionnel responsable de B. Akhtar-Zaidi et al [1] révèlent que ces SNP, enrichis dans des régions enhancers marquées par H3K4me1 et spécifiques aux cellules de la crypte, sont détectés dans des régions de VEL acquis ou perdus dans les cellules CCR.…”
unclassified